2014
DOI: 10.1371/journal.pone.0100423
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Ability and Fitness Differences between Two Introduced Populations of the Invasive Whitefly Bemisia tabaci Q in China

Abstract: BackgroundOur long-term field survey revealed that the Cardinium infection rate in Bemisia tabaci Q (also known as biotype Q) population was low in Shandong, China over the past few years. We hypothesize that (1) the Cardinium-infected (C +) B. tabaci Q population cannot efficiently compete with the Cardinium-uninfected (C −) B. tabaci Q population; (2) no reproductive isolation may have occurred between C + and C −; and (3) the C − population has higher fitness than the C + population.Methodology and ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 58 publications
1
39
1
Order By: Relevance
“…However, the authors did not control for host genotype, which makes it difficult to distinguish how much of the difference seen is due to Cardinium relative to host differences coincidentally associated with Cardinium infection. Cardinium was not shown to manipulate reproduction or sex ratios in this study (Fang et al 2014).…”
Section: • Effect Of Symbionts On Host Sex Ratio -Bacterial Endosymbicontrasting
confidence: 60%
See 1 more Smart Citation
“…However, the authors did not control for host genotype, which makes it difficult to distinguish how much of the difference seen is due to Cardinium relative to host differences coincidentally associated with Cardinium infection. Cardinium was not shown to manipulate reproduction or sex ratios in this study (Fang et al 2014).…”
Section: • Effect Of Symbionts On Host Sex Ratio -Bacterial Endosymbicontrasting
confidence: 60%
“…tabaci MED whiteflies were infected with Cardinium in Shandong, China. After establishing infected and uninfected lines in the laboratory (all fixed for Portiera and Hamiltonella), Fang et al (2014) found that uninfected whiteflies greatly outnumber infected individuals after a few generations, and have higher growth rates, indicating that Cardinium may be detrimental to its host. However, the authors did not control for host genotype, which makes it difficult to distinguish how much of the difference seen is due to Cardinium relative to host differences coincidentally associated with Cardinium infection.…”
Section: • Effect Of Symbionts On Host Sex Ratio -Bacterial Endosymbimentioning
confidence: 99%
“…We hypothesized that our test population of Eastern MED (Q2), collected from a residence in Palm Beach County, would demonstrate a competitive disadvantage on tomato in relation to MEAM1 as MED had in China. However, given that the pest status of MED populations can be influenced by endosymbiont fauna, host plant, and history of exposure to insecticides, it is difficult to predict how MED populations in Florida will behave based on information derived from countries where growing conditions are in many ways distinct from Florida (Fang et al 2014;Mouton et al 2014;Fujiwara et al 2015;Su et al 2016). In addition, we present the results of probit analysis for imidacloprid and thiamethoxam tolerance from 2 MED populations collected from hibiscus (Hibiscus rosa-sinensis L.; Malvaceae) in Palm Beach County, and 13 MEAM1 populations collected from commercial vegetable fields in south Florida between late 2016 and mid-2017.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular bacterium “ Ca. Cardinium hertigii” 1 (hereafter Cardinium ) is an intriguing arthropod symbiont capable of reproductive manipulation 2 3 4 5 or of determining effects ranging from stimulation of the host’s immune response 6 , to fecundity benefits 5 7 , or even to reduction of the host’s fitness 8 .…”
mentioning
confidence: 99%